Plant species diversity and forage quality as affected by pasture management and simulated cattle activities. Issue 4 (20th May 2014) - Yoshihara, Yu; Okada, Miya; Sasaki, Takehiro; Sato, Shusuke
Abstract: Grazed pastures have been historically used in Japan for animal production with little concern to biodiversity. However, pasturing has significant effects on biodiversity and productivity because it produces gaps in the distribution of vegetation due to animal activities. We hypothesized that different grazing activities would have effects on the diversity of plant species and forage quality in different ways and that the sward type would modify these effects. Therefore, we attempted to predict the diversity of plant species and changes in total nutrient content per area at the time since treatment on the basis of simulations of cattle activities in three pastures with different vegetation compositions. We created three ground types (grazed areas, cleared ground, and undisturbed areas) in three pastures (improved, partially improved semi‐natural, and semi‐natural pasture) and recorded the percentage cover of each plant within the plots. We repeatedly calculated the biodiversity indices from these community data by varying the sampling probabilities for each ground type, which provided us with the expected species diversity indices with the changing proportions of each ground type. Furthermore, we investigated the dry matter and forage qualities. For improved and partially improved semi‐natural pasture, our models predicted that plant diversity increased as a saturating function of the proportion of cleared ground and grazed area relative to the undisturbed area, although our models also showed exponential curves for the semi‐natural pasture. Forage samples from cleared ground plots and semi‐natural pasture had the lowest forage quality among all pastures. Based on the predicted effects of cattle pasturing on the plant species biodiversity and forage quality, it may be more beneficial to maintain a small proportion of cleared ground in the improved pasture during intensive grazing.